Digital Leisure: An Opportunity for Intergenerational Well-Being in Times of Pandemic? - Rosa Ana Alonso Ruiz; Magdalena Sáenz de Jubera Ocón; María Ángeles Valdemoros San Emeterio; Ana Ponce de León Elizondo (Springer, 2022)
Leisure activities shared by grandparents and grandchildren provide important benefits. The health and humanitarian crisis caused by the coronavirus (COVID-19) pandemic has made it necessary to use digital tools to alleviate the lack of contact between adults and children. This paper had as its aim to identify the digital leisure shared by grandparents and their pre-adolescent grandchildren (10-12 years old) before and during the pandemic, as well as its contribution to intergenerational well-being from a holistic paradigm, ultimately aiming to determine whether that digital leisure constitutes an experience of human development for young and old people alike. The sample was made up of 153 grandparents of 10-to-12-year-old children living in the north of Spain. Alongside the use of an ad hoc questionnaire, descriptive and inferential analyses were carried out. Most intergenerational leisure activities ceased to be performed during the lockdown, except for those that could be carried out remotely, thanks to information and communication technologies, which ensured the continuity of social and family interactions. Technological connectivity between generations provided greater support to communication and meaningful relationships, additionally facilitating active aging processes.